Illegal wildlife trade: Scale, processes, and governance - ‘T Sas-Rolfes, M; Challender, D; Hinsley, A; Veríssimo, D; Milner-Gulland, E (Annual Reviews, 2019)
Illegal wildlife trade (IWT) has increased in profile in recent years as a global policy issue, largely because of its association with declines in prominent internationally trafficked species. In this review, we explore the scale of IWT, associated threats to biodiversity, and appropriate responses to these threats. We discuss the historical development of IWT research and highlight the uncertainties that plague the evidence base, emphasizing the need for more systematic approaches to addressing evidence gaps in a way that minimizes the risk of unethical or counterproductive outcomes for wildlife and people. We highlight the need for evaluating interventions in order to learn, and the importance of sharing datasets and lessons learned. A more collaborative approach to linking IWT research, practice, and policy would better align public policy discourse and action with research evidence. This in turn would enable more effective policy making that contributes to reducing the threat to biodiversity that IWT represents.